Pengaruh Penerapan Model STAD Dalam Meningkatkan Hasil Belajar Materi Jaringan Telekomunikasi - Hari Anna Lastya; Ghufran Ibnu Yasa; Khairil Amri (PTE FTK UIN Ar-Raniry, 2021)
A previous observations has been conducted at SMK Negeri 5 Telkom Banda Aceh, before run the research. The previous data showed that the school had implemented a learning process that was divided into study groups, but not categorized as student centered learning. Based on this reason, the research conducted with applying the STAD (student Team Achievement Division) type of cooperative learning. Theoretically, STAD is one of the model that involved students active. The purpose of this study, to determine the effect of the STAD type model in improving student learning outcomes on telecommunication network subject. The sample involved in the study is the class that has a lower pre-test score than the other classes. The instrument used were tests and observations. The results showed that the average value in the experimental class after the STAD model was applied was 80.75, while the control class has the average in 46.1. in terms of hypotheses results, Ha was accepted and Ho was rejected because the results of the t-test obtained tcount > ttable (8.3 > 2.66). Thus, the STAD models provides better learning outcomes than the konventional model.